The Role of Strategy Management Mechanisms to Increasing Competitiveness - Bosas, Antanas (Ekonomika, 1999)
The problem of increasing competitiveness of diversificated organisations interrelates with the manager’s skill to employ the strategy management mechanisms in corporation management practice.The role of manager in usage of the possibility of the synergy effects and the sources of these effects are discussed. The management practice is analysed and the generalised concept of seek to get synergy effect in corporation is proposed.The importance of corporation manager’s intercourse logic for conciliation interests of influence groups is discussed. The profit on using of predominate collaboration logic is investigated, and the positive examples of put this logic in corporation management practice is discussed. On the basis of using predominant collaboration logic inside the country for increasing competitiveness outside country the concept of wording compatible strategy for transit through Klaipėda seaport is proposed.